1996
DOI: 10.1128/aem.62.2.367-371.1996
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Chlorinated Dibenzofurans and Dibenzo-p-Dioxins by Sphingomonas sp. Strain RW1

Abstract: The ability of the dibenzofuran-and dibenzo-p-dioxin-mineralizing bacterium Sphingomonas sp. strain RW1 (R.-M. Wittich, H. Wilkes, V. Sinnwell, W. Francke, and P. Fortnagel, Appl. Environ. Microbiol. 58:1005-1010, 1992) to oxidize chlorinated derivatives of dibenzofuran and dibenzo-p-dioxin was analyzed. Strain RW1 degraded several mono-and dichlorinated dibenzofurans and dibenzo-p-dioxins, but it did not degrade more highly chlorinated congeners. Most mono-and dichlorinated dibenzofurans and dibenzo-p-dioxins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
58
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(58 citation statements)
references
References 41 publications
0
58
0
Order By: Relevance
“…Dioxin-degrading bacteria discovered so far do not show a full dioxin-degrading ability in the presence of other carbon sources or other bacteria in nature. It appears that the intermediates of PCDDs and PCDFs, such as chlorocatechols, inhibit enzymes catalyzing the degradation reaction [16]. Therefore, it is essential to elucidate the mechanism of regulation and substrate recognition of dioxin-degrading enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Dioxin-degrading bacteria discovered so far do not show a full dioxin-degrading ability in the presence of other carbon sources or other bacteria in nature. It appears that the intermediates of PCDDs and PCDFs, such as chlorocatechols, inhibit enzymes catalyzing the degradation reaction [16]. Therefore, it is essential to elucidate the mechanism of regulation and substrate recognition of dioxin-degrading enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent study of dioxin-degrading bacteria, Sphingomonas wittichii was found to have a GSL pro¢le identical to that of S. yanoikuyae. S. wittichii was isolated from the water of the Elbe River as a dioxin degrader [10] and its dioxin metabolism [11,12] as well as taxonomic position [13] have been studied intensively. The membrane permeability of such substances is an important factor in the ability to degrade dioxins and other hydrophobic substances, and it may correlate with the pro¢le and the structure of membrane lipids, especially those of GSL.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, attention has been directed toward developing technology to clean up these environmental pollutants by bioremediation [3][4][5][6][7][8][9][10][11][12]. Rapid advances have also been made in the analysis of dioxins in the field of environmental biotechnology.…”
Section: Introductionmentioning
confidence: 99%